2020
DOI: 10.21203/rs.2.18723/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring the durability of the Long-Lasting Insecticidal Nets MAGNet and Royal Sentry in three ecological zones of Mozambique

Abstract: Background Malaria prevention with long-lasting insecticidal nets (LLINs) has seen a tremendous scale-up in sub-Saharan Africa in the last decade. To sustain this success, it is important to understand how long LLINs remain in the households and continue to protect net users, which is termed durability. This information is needed to decide the appropriate timing of LLIN distribution and also to identify product(s) that may be underperforming relative to expectations. Following guidance from the U.S. President’… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Each hole (size 4 cm × 4 cm) was spaced evenly along the length of each side panel, with nine holes in two rows on each long side and six on each short side. This differs from the current WHO guidelines [27]; it is not unusual for nets to acquire this number of holes in use and remain functional [18,28] (it is also more comfortable for the calf, which generates considerable heat). This also improves the power to detect a difference in blood feeding inhibition between the treatment arms of the trial and the control.…”
Section: Preparation Of Mosquito Net Treatmentsmentioning
confidence: 73%
“…Each hole (size 4 cm × 4 cm) was spaced evenly along the length of each side panel, with nine holes in two rows on each long side and six on each short side. This differs from the current WHO guidelines [27]; it is not unusual for nets to acquire this number of holes in use and remain functional [18,28] (it is also more comfortable for the calf, which generates considerable heat). This also improves the power to detect a difference in blood feeding inhibition between the treatment arms of the trial and the control.…”
Section: Preparation Of Mosquito Net Treatmentsmentioning
confidence: 73%
“…contributing to attrition rather than non-use. Household acquisition of additional LLINs during the study periods was not systematically recorded in these studies, but some of the cohort LLINs were taken out of use because newer, non-cohort LLINs became available and this has been shown to be an important determinant of attrition rates [ 31 – 33 ]. Chemical decay is evidently not an important reason for either attrition or non-use, since for the LLIN brands included in this investigation, the insecticidal effects are generally retained through 3 years (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The country by country analysis had revealed a number of variables describing net use environment and net care as significant determinants of survival of LLIN in serviceable condition [15,19,23,31] and a recent pooled analysis has confirmed that some of these are strong predictors across countries [26]. Using these previously established determinants in a Cox regression of LLIN survival (Table 3) shows a significant protective effect of the RD metric suggesting that every increase of the RD score by 10 points reduced the hazard of failure by 36% (adjusted hazard ratio (aHR) 0.64).…”
Section: Resultsmentioning
confidence: 99%